Influence of high-frequency radiation on turbulence measurements on a 200 m tower - Christian Barthlott; Norbert Kalthoff; Franz Fiedler (Meteorologische Zeitschrift, 2003)
Turbulence measurements conducted by means of Solent Gill ultrasonic anemometers at several altitudes on the 200 m tower at the Research Center Karlsruhe showed white noise behaviour at the high-frequency end of the spectra with increasing measurement height. In a number of data sets with a time resolution of 48 ms, the computed power spectra of the velocity components and temperature converge into white noise and the decline in the inertial subrange expected theoretically is hidden. The noise covers a broad range of the spectrum, which greatly increases variance and makes further data analysis difficult. The cause of this parasitic noise is found in high-frequency radiation from regional longwave transmitters in the frequency range of 150 to 200 kHz, which interferes with the transducer crystals. The resonance frequency of the transducer crystals is 180 kHz. It is found that a thin, grounded mesh wire around the sensor head acts like a Faradays cage, protecting the transducers from the radiation. Negative side effects, like eddy production from the cage or a modified mean wind speed can be excluded from results gained by different ultrasonic anemometers, operated simultaneously close to the ground. The mesh wire shield thus is a permanent solution to these problems in case of longwave transmitters surrounding the measurement site.